Perilaku Penggunaan Berkelanjutan Bank Digital - Rinwantin, Rinwantin; Hidayatullah, Suryakusuma Kholid (ITB AAS Indonesia Surakarta, 2024)
This research will examine post-adoption of Digital Banks in terms of performance expectancy and effort expectancy variables. This study aims to examine more deeply the post-adoption of Digital Banks, looking for the effect of performance expectancy, effort expectancy through perceived behavioral control on the use of sustainable Digital Banks. This needs to be done because Digital Banks are currently still in a business model and do not yet have their own special regulations regarding their management. A relatively large initial investment certainly expects profitable sustainable use. The method is quantitative research, and use SEM PLS for analyze.The result is PE has a positive and significant effect on PBC (β: 0.319, P values: 0.004), EE has a positive and significant effect on PBC (β: 0.621, P values: 0.000) and PBC has a positive and significant effect on UB (β: 0.820, P values: 0.000). the implication is important for digital banks to continue to provide important and up-to-date information on a regular basis through notifications available on digital banks. When there is a development of feature innovation, digital banks still have to simplify the flow that must be followed so that sustainable use of digital banks can be achieved. Keywords: Digital Banks, Perfomance Expectancy, Effort